STUDI KOMPOSISI, STRUKTUR, DAN ASOSIASI TUMBUHAN SEKITAR PASAK BUMI (Eurycoma longifolia) DI AREAL IUPHHK PT. AUSTRAL BYNA KALIMANTAN TENGAH - Fachri Rahmadani Pratama; Yudi Firmanul Arifin; Adistina Fitriani (Jurnal Sylva Scienteae, 2021)
Eurycoma longifolia is a medicinal plant that almost all parts can be utilized. However, this type of plant has begun to diminish in the habitat of natural forests, as the harvesting continues to increase, while the effort is not done. In the future cultivation effort, then the research on the Sturuktur, plant composition around the Eurycoma longifolia and also the associated plants is very necessary, especially cultivation in the day. Primary data sampling activities are done by single tile method with tile size used is 100 × 60 m.  Furthermore, in the single plot, there are 15 observation plots for tree level, pole, stake, and bottom plant. The determination of the observation plot is done purposive sampling (intentional) in the area that there are many Earth stakes in each different location. The results of the study found there were about 50 types of vegetation in community units, Semai benih Bangsa 18 types, stakes 26 types, pole 23 types, and trees 25 types. The Association of Plant Stakes of the Earth with 5 dominant types at the tree level there is no association.Keywords: Pasak bumi, composition, structure, association